BACHELOR DEGREE OR BACHELOR: THE CRITERIA FOR CHOOSING ACADEMIC OF THE COURSE OF PHYSICAL EDUCATION UNIDAVI. (Fiep Bulletin - online, 2015)
This study aims to examine the criteria used by students of Physical Education UNIDAVI, for the same choice. We propose a reflection so we suggest choosing the Bachelor Degree or, taking into consideration all necessary for proper and worried about the future professional teacher training priorities, without forgetting the orientation in life in society for the common good. The students of Physical Education UNIDAVI be searched - University for Development of Alto Vale do Itajaí, where a semi-structured interview questions prepared in advance will be made according LAVILLE (. 1999, p 333) semi-structured interview "is series of open questions asked orally in an expected order, but in which the interviewer has the possibility of adding questions for clarification. "This study will have completed its development in 2015. Physical education has been characterized in recent times by the scope and ramifications of attractive jobs. The great supporter of the career choice of many young people's sport, but the physical training, physical activity focused on the health and quality of life, are the reasons for choosing the professional branch. In another aspect, a career school teacher seems to be a more stable monthly financial choice of employment. Given all that, many young people are at the doors of the labor market and so many others in more difficult circumstances, are forced to choose since the vestibular their academic and professional option, with concerns about the size and diversity involving both professional licensure as baccalaureate. The demands in the labor market beyond the borders of the undergraduate course and traverse the path of continuing education to stay alive in the working world.
Keywords: bachelor degree; Bachelor; Physical Education